Anti-Inflammatory and Organ-Protective Effects of Resveratrol in Trauma-Hemorrhagic Injury - Fu-Chao Liu; Yung-Fong Tsai; Hsin-I Tsai; Huang-Ping Yu (Hindawi Limited, 2015)
Resveratrol, a natural polyphenolic compound of grape and red wine, owns potential anti-inflammatory effects, which results in the reduction of cytokines overproduction, the inhibition of neutrophil activity, and the alteration of adhesion molecules expression. Resveratrol also possesses antioxidant, anti-coagulation and anti-aging properties, and it may control of cell cycle and apoptosis. Resveratrol has been shown to reduce organ damage following traumatic and shock-like states. Such protective phenomenon is reported to be implicated in a variety of intracellular signaling pathways including the activation of estrogen receptor, the regulation of the sirtuin 1/nuclear factor-kappa B and mitogen-activated protein kinases/hemeoxygenase-1 pathway, and the mediation of proinflammatory cytokines and reactive oxygen species formation and reaction. In the recent studies, resveratrol attenuates hepatocyte injury and improves cardiac contractility due to reduction of proinflammatory mediator expression and ameliorates hypoxia-induced liver and kidney mitochondrial dysfunction following trauma and hemorrhagic injuries. Moreover, through anti-inflammatory effects and antioxidant properties, the resveratrol is believed to protect organ function in trauma-hemorrhagic injury. In this review, the organ-protective and anti-inflammatory effects of resveratrol in trauma-hemorrhagic injury will be discussed.